Diseño de un taller mediante el uso de pictogramas que permita el desarrollo del lenguaje dirigido a niños y niñas de 3-4 años de edad en el centro infantil del buen vivir “Luis Fernando Ruiz” en la ciudad de Latacunga, provincia de Cotopaxi en el periodo 2013-2014 - Amaya Guilcamaigua, Mercy Alexandra (2014)
The present thesis had a purpose to do pictograms based on methodological and ludic strategies destined to a better teaching, it was done in a correct way thanks a good investigation, this was possible when a problem in the society was detected so that a feasible solution can be given, because the society has many problems in the education of children, a better learning, development of their abilities and creativity. The problem was found at the “Luis Fernando Ruiz” Good Living Center, it had a great reception, who were willing to receive this helping with several investigative techniques and methodologies that have been used a tool for facilitating the execution of this thesis. The theoretical and practical foundation was done with the cooperation of teachers, parents, children and the coordinator of ”Luis Fernando Ruiz Good Living Child Center” who contribute to make the pictograms, the investigative development has helped to formulate conclusion and recommendations which facilitated to conclude the thesis satisfactorily and to find a solution to the problem on the development of language and the corresponding thesis.